2013
DOI: 10.1016/j.ijnurstu.2012.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Sense of coherence is a predictor of perceived health in adolescents with congenital heart disease: A cross-lagged prospective study

Abstract: Evidence was obtained for reciprocal pathways between SOC and the domains of perceived health, although the predominant direction of effects was found to be from SOC to perceived health. Hence, improving SOC has the potential to enhance future perceived health of adolescents with CHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
61
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(67 citation statements)
references
References 52 publications
4
61
1
1
Order By: Relevance
“…This theory explains the relationship between stressors, coping and health and can be measured by the SOC scale 30 . In a study examining SOC among adolescents with congenital heart disease, results show a relation between low SOC and negatively perceived health 31 . Furthermore, young adults who had an occurrence of epileptic seizure scored lower on the SOC scale than those that were seizure free 32 .…”
Section: Discussionmentioning
confidence: 99%
“…This theory explains the relationship between stressors, coping and health and can be measured by the SOC scale 30 . In a study examining SOC among adolescents with congenital heart disease, results show a relation between low SOC and negatively perceived health 31 . Furthermore, young adults who had an occurrence of epileptic seizure scored lower on the SOC scale than those that were seizure free 32 .…”
Section: Discussionmentioning
confidence: 99%
“…This finding correlates with those of other studies. Among adolescents with congenital heart disease, the QOL was significantly higher compared with the control group [26]. It has been suggested that QOL and health are two separate constructs, although they are not mutually exclusive [7], something that could explain why persons with epilepsy are reporting high quality of life in spite of being affected by epilepsy.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, SOC has been identified as a determinant of QOL, over time, in female survivors of acute myocardial infarction [31] and an important resource for quality of life among patients with congenital heart disease [26]. The SOC concept is considered to be a health resource influencing QOL [30,31], and it has been suggested that a salutogenic approach in clinical practice, focusing on patient resources and strengths rather than on problems and limitations, could optimize the QOL for people affected by epilepsy [31].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, people with a strong SOC perceive the world as (i) comprehensible, (ii) manageable, and (iii) meaningful [47]. Previous studies in patients with CHD have highlighted the importance of considering sense of coherence in relation to PROs [48,49]. Therefore, sense of coherence is evaluated in this study using the 13-item Orientation to Life Questionnaire [47,50].…”
Section: Secondary Outcomesmentioning
confidence: 99%